Faith-Based Humanitarianism: Organizational Change and Everyday Meanings in South Africa - Burchardt, Marian (Sociology of religion, 2013)
Engaging and challenging central institutionalist concepts, this article focuses on the involvement of churches and other Christian organizations in HIV/AIDS programs in South Africa in order to analyze the ensuing organizational dynamics. It argues that the asymmetrical power relations between mostly Northern donors and local churches, within which these organizational dynamics unfold, engender two interlocked processes: on the one hand, institutional isomorphism, which is reflected in the adoption by local actors of the technocratic and official templates promoted by the dominant discourse on civil society and its main protagonist, the nongovernmental organization; and on the other hand, local actors' deployment of strategies of extraversion that contradict the “paper versions” of faith-based development. This article analyzes how the resulting contradictions are played out and shows how both the compliance with, and the strategic refractions of, organizational templates depend on one another.